Genome-based transmission modelling separates imported tuberculosis from recent transmission within an immigrant population. Issue 10 (14th September 2018) - Ayabina, Diepreye; Ronning, Janne O.; Alfsnes, Kristian; Debech, Nadia; Brynildsrud, Ola B.; Arnesen, Trude; Norheim, Gunnstein; Mengshoel, Anne-Torunn; Rykkvin, Rikard; Dahle, Ulf R.; Colijn, Caroline; Eldholm, Vegard
Abstract : In many countries the incidence of tuberculosis (TB) is low and is largely shaped by immigrant populations from high-burden countries. This is the case in Norway, where more than 80 % of TB cases are found among immigrants from high-incidence countries. A variable latent period, low rates of evolution and structured social networks make separating import from within-border transmission a major conundrum to TB control efforts in many low-incidence countries. Clinical Mycobacterium tuberculosis isolates belonging to an unusually large genotype cluster associated with people born in the Horn of Africa have been identified in Norway over the last two decades. We modelled transmission based on whole-genome sequence data to estimate infection times for individual patients. By contrasting these estimates with time of arrival in Norway, we estimate on a case-by-case basis whether patients were likely to have been infected before or after arrival. Independent import was responsible for the majority of cases, but we estimate that about one-quarter of the patients had contracted TB in Norway. This study illuminates the transmission dynamics within an immigrant community. Our approach is broadly applicable to many settings where TB control programmes can benefit from understanding when and where patients acquired TB.